28 new pre-breeding wheat lines with high yield potential and climate resilience for Mexico's growing regions. - CGIAR Research Program on Wheat (2018)
Early discovery/successful identification of outstanding wheat lines, with potential impact due to its high yield and climate resilience traits. Said lines have been tested on-station.